TOB1 modulates neutrophil phenotypes to influence gastric cancer progression and immunotherapy efficacy - Zhang, Jinfeng; Li, Yunlong; Chen, Jing; Huang, Tongtong; Lin, Jing; Pi, Yilin; Hao, Huiting; Wang, Dong; Liang, Xiao; Fu, Songbin; Yu, Jingcui (Frontiers in Immunology, 2024)
The ErbB-2.1(TOB1) signaling transducer protein is a tumor-suppressive protein that actively suppresses the malignant phenotype of gastric cancer cells. Yet, TOB1 negatively regulates the activation and growth of different immune cells. Understanding TOB1's expression and role in gastric cancer immune environment is crucial to maximize its potential in targeted immunotherapy. This study employed multiplex immunofluorescence analysis to precisely delineate and quantify the expression of TOB1 in immune cells within gastric cancer tissue microarrays. We remarkably revealed that TOB1 exhibits varying expression levels in both the nuclei (nTOB1) and cytoplasm (cTOB1) of diverse immune cell populations, including CD8 + T cells, CD66b + neutrophils, FOXP3 + Tregs, CD20 + B cells, CD4 + T cells, and CD68 + macrophages within gastric cancer and adjacent tissues. Significantly, TOB1 was notably concentrated in CD66b + neutrophils. Survival analysis showed that a higher density of cTOB1/nTOB1 + CD66b + neutrophils linked to a better prognosis. Subsequent experiments revealed that, following stimulation with the supernatant of tumor tissue culture, the levels of TOB1 protein and mRNA in neutrophils decreased, accompanied by enhanced apoptosis. HL-60 cells were induced to neutrophil-like cells by DMSO. Neutrophils-like cells with attenuated TOB1 gene expression by si-TOB1 demonstrated heightened apoptosis, consequently fostering a malignant phenotype in AGS and HCG-27 cells upon co-cultivation. The subsequent analysis of the datasets from TCGA and TIMER2 revealed that patients with high level of TOB1 combined neutrophils showed better immunotherapy response. This study significantly advances our comprehension of TOB1's role within the immune microenvironment of gastric cancer, offering promising therapeutic targets for immunotherapy in this context.